A case of trichoblastic carcinosarcoma with review of literature - Indu M. Nair; Deepa Gharpuray-Pandit; Claribel Cardozo (Elsevier, 2021)
Trichoblastic carcinosarcoma is a rare biphasic malignant neoplasm showing trichogenic differentiation. The tumour shows both malignant epithelial and stromal components. A review of literature has shown that only ten cases have been reported so far. This could be due to under-recognition of this tumour or under-reporting of this entity. We report a further case of trichoblastic carcinosarcoma. Ours is a busy tertiary care centre with plastic surgery service and this is the first case diagnosed in our department over a period of fifteen years.